HUBUNGAN SELF-ESTEEM DENGAN SELF-DISCLOSURE PENGGUNA SECOND ACCOUNT PADA USIA DEWASA AWAL - Angelique Shifra Putri; Doddy Hendro Wibowo (Journal of Innovation Research and Knowledge, 2025)
Self-esteem serves as one of the factors influencing self-disclosure when using second account Instagram. This study aims to examine the relationship between self-esteem and self-disclosure among second account users in early adulthood. This research employs a quantitative approach using Pearson product-moment correlation method. The research subject consisted of 190 participants who were second account Instagram users aged 18-25 years in Indonesia, selected through snowball sampling technique. Self-esteem measurement utilized the RSES (Rosenberg's Self-esteem Scale) and self-disclosure was measured using an adapted scale from the RSDS (Revised Self-disclosure Scale). The results indicated that there was no significant relationship between self-esteem and self-disclosure, with a correlation value of -0.022 and a significance value of 0.759 (p>0.05). The implications of this research contribute to theoretical development by suggesting that there are other factors with greater contributions than self-esteem that influence self-disclosure